Physiological characteristics of IRR 400 series rubber clones (Hevea brasiliensis Muell. Arg.) under drought stress [version 4; peer review: 1 approved, 2 approved with reservations] - Mohammad Basyuni; Yaya Hasanah; Syarifah Aini Pasaribu; Edison Purba (F1000Research)
Background Drought stress is one of the main causes of plant death. Strategies for plants survival are morphological adaptations, specific signaling pathways, and tolerance mechanisms. Rubber plantations have many uses, such as foreign exchange sources, job sources, forest revitalization, and a source of alternative wood for building materials and furniture. The rubber plant’s response to drought stress is a complex biological process. A tolerant rubber clone in a dry area is the right approach. The present study aimed to identify drought tolerant traits in order to select or identify drought-tolerant clones at juvenile stage. Methods The first factor examined for this work was clones (IRR 425, IRR 428, IRR 429, IRR 434, IRR 440, RRIC 100, and BPM 24) and the second factor was water content (30%, 60%, and 90%). The study was arranged on a factorial randomized block design and repeated three times. Characteristics observed were total sugar (µM), proline (mg/L), chlorophyll a, b, total (µg/mL), hydrogen peroxidase (µmol/g), ascorbate peroxidase (unit/mg), superoxide dismutase (unit/mg), and peroxide dismutase (unit/mg). Results The tolerance ability of the IRR 400 series rubber clones to drought stress was determined by observing the characteristics of sugar total and proline. The concentration of total sugar and proline were higher when the plant was treated with a lower water content. The selected clones tolerant to drought stress are RR 425 and IR 434 with high total sugar content and proline. Other characteristics, namely chlorophyll a, b, and total, as well as hydrogen peroxidase, ascorbate peroxidase, super oxide dismutase, peroxide dismutase, cannot be used as selection characteristics for this study. Conclusions This drought study of IRR 400 clones with varying water content percentages illustrated that the total sugar and proline characteristics could be used to distinguish tolerance levels from other observed characteristics.